Implementasi Konsep “Muni Papua Bageka Tota Kabo Wado Make” pada Interior Museum Negeri Provinsi Papua di Waena, Jayapura - Jessica Andini Gosal; Ronald Hasudungan Irianto Sitindjak; Linggajaya Suryanata (Intra, 2017)
Papua Province State Museum is one of the museums located in Jayapura, Papua which has approximately 3600 collections of art and culture from Papua and West Papua. In fact, this museum is less desirable to visit the public due to the condition of the museum's interior and the presentation of less attractive collections and good maintenance and technical buildings, especially electricity that is unstable so the need for redesain museum for the interior of value and interesting. To achieve this, the redesign of this museum takes the concept of